2007
DOI: 10.1016/j.mcn.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

KRIP6: A novel BTB/kelch protein regulating function of kainate receptors

Abstract: Whereas many interacting proteins have been identified for AMPA and NMDA glutamate receptors, fewer are known to directly bind and regulate function of kainate receptors. Using a yeast two-hybrid screen for interacting partners of the C-terminal domain of GluR6a, we identified a novel neuronal protein of the BTB/kelch family, KRIP6. KRIP6 binds to the GluR6a C-terminal domain at a site distinct from the PDZ-binding motif and it co-immunoprecipitates with recombinant and endogenous GluR6. Co-expression of KRIP6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…1). At least six genes may be involved in brain development and function, particularly: DCUN1D1, for which the mouse ortholog is expressed in proliferating neuroblasts [4]; DVL3, a regulator of cell proliferation and neuroblast specification [5]; several genes belonging to the serotonin receptor family (HTR3C, HTR3D, HTR3E); KLHL24, involved in functional regulation of glutamate receptors [6]; MAP6D1, a neuronal protein that binds microtubules and plays a role in synaptic function in neuritis [7].…”
Section: Discussionmentioning
confidence: 99%
“…1). At least six genes may be involved in brain development and function, particularly: DCUN1D1, for which the mouse ortholog is expressed in proliferating neuroblasts [4]; DVL3, a regulator of cell proliferation and neuroblast specification [5]; several genes belonging to the serotonin receptor family (HTR3C, HTR3D, HTR3E); KLHL24, involved in functional regulation of glutamate receptors [6]; MAP6D1, a neuronal protein that binds microtubules and plays a role in synaptic function in neuritis [7].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that the specific behavior of synaptic KARs could be determined by the binding of modulatory proteins to the receptors' cytoplasmic domains. However, the alterations of KAR gating properties induced by interacting proteins reported so far are unlikely to be the main determinant for the differences between KAR-EPSCs and recombinant KAR-mediated currents (Garcia et al, 1998;Bowie et al, 2003;Laezza et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…Conversely, Y2H screens have provided evidence for a direct interaction between GluK2a and PDZ domaincontaining proteins (PSD-95, syntenin, GRIP, and PICK1) (21,22), through the last four amino acids of GluK2a. In addition, two proteins of the BTB-Kelch family, actinfilin and KRIP6, bind to the C-terminal domain of GluK2a (10,23), although the exact sequence of interaction has not been identified. Finally, a recent study has indicated that Neto2, identified by a Y2H screen acts as an auxilliary protein for KARs (24).…”
Section: Discussionmentioning
confidence: 99%